Interleukin-7 Biology and Its Effects on Immune Cells: Mediator of Generation, Differentiation, Survival, and Homeostasis - Chen, Deng; Tang, Ting-Xuan; Deng, Hai; Yang, Xiang-Ping; Tang, Zhao-Hui (Frontiers in Immunology, 2021)
Interleukin-7 (IL-7), a molecule known for its growth-promoting effects on progenitors of B cells, remains one of the most extensively studied cytokines. It plays a vital role in health maintenance and disease prevention, and the congenital deficiency of IL-7 signaling leads to profound immunodeficiency. IL-7 contributes to host defense by regulating the development and homeostasis of immune cells, including T lymphocytes, B lymphocytes, and natural killer (NK) cells. Clinical trials of recombinant IL-7 have demonstrated safety and potent immune reconstitution effects. In this article, we discuss IL-7 and its functions in immune cell development, drawing on a substantial body of knowledge regarding the biology of IL-7. We aim to answer some remaining questions about IL-7, providing insights essential for designing new strategies of immune intervention.